Long term effect of reduced pack sizes of paracetamol on poisoning deaths and liver transplant activity in England and Wales: interrupted time series analyses. - Hawton, K; Bergen, H; Simkin, S; Dodd, S; Pocock, P; Bernal, W; Gunnell, D; Kapur, N (2013)
OBJECTIVE: To assess the long term effect of United Kingdom legislation introduced in September 1998 to restrict pack sizes of paracetamol on deaths from paracetamol poisoning and liver unit activity. DESIGN: Interrupted time series analyses to assess mean quarterly changes from October 1998 to the end of 2009 relative to projected deaths without the legislation based on pre-legislation trends. SETTING: Mortality (1993-2009) and liver unit activity (1995-2009) in England and Wales, using information from the Office for National Statistics and NHS Blood and Transplant, respectively. PARTICIPANTS: Residents of England and Wales. MAIN OUTCOME MEASURES: Suicide, deaths of undetermined intent, and accidental poisoning deaths involving single drug ingestion of paracetamol and paracetamol compounds in people aged 10 years and over, and liver unit registrations and transplantations for paracetamol induced hepatotoxicity. RESULTS: Compared with the pre-legislation level, following the legislation there was an estimated average reduction of 17 (95% confidence interval -25 to -9) deaths per quarter in England and Wales involving paracetamol alone (with or without alcohol) that received suicide or undetermined verdicts. This decrease represented a 43% reduction or an estimated 765 fewer deaths over the 11andfrac14; years after the legislation. A similar effect was found when accidental poisoning deaths were included, and when a conservative method of analysis was used. This decrease was largely unaltered after controlling for a non-significant reduction in deaths involving other methods of poisoning and also suicides by all methods. There was a 61% reduction in registrations for liver transplantation for paracetamol induced hepatotoxicity (-11 (-20 to -1) registrations per quarter). But no reduction was seen in actual transplantations (-3 (-12 to 6)), nor in registrations after a conservative method of analysis was used. CONCLUSIONS: UK legislation to reduce pack sizes of paracetamol was followed by significant reductions in deaths due to paracetamol overdose, with some indication of fewer registrations for transplantation at liver units during the 11 years after the legislation. The continuing toll of deaths suggests, however, that further preventive measures should be sought.